2017
DOI: 10.1051/0004-6361/201731499
|View full text |Cite
|
Sign up to set email alerts
|

The MUSEHubbleUltra Deep Field Survey

Abstract: Non-resonant Fe ii* (λ2365, λ2396, λ2612, λ2626) emission can potentially trace galactic winds in emission and provide useful constraints to wind models. From the 3.15 × 3.15 mosaic of the Hubble Ultra Deep Field (UDF) obtained with the VLT/MUSE integral field spectrograph, we identify a statistical sample of 40 Fe ii* emitters and 50 Mg ii (λλ2796, 2803) emitters from a sample of 271 [O ii]λλ3726, 3729 emitters with reliable redshifts from z = 0.85 − 1.50 down to 2 × 10 −18 (3 σ) ergs s, covering the M range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 72 publications
13
70
0
Order By: Relevance
“…We also identify a strong C iii] emitter in the southwest of the cluster (ID 4139; z = 1.9655) with a bright UV continuum and several other emission and absorption features, including Fe ii * [λ ∼ 2400,λ ∼ 2600] emission, which is useful for probing galactic winds (see e.g. Finley et al 2017). Additionally, we identify a fourth potential C iii] emitter (ID 11481; z = 2.5607) in the northeast, and three objects with weak UV absorption features (ID 6655; z = 2.1240, ID 13600; z = 2.5442, and ID 14822; z = 2.8897) at the western edges of the mosaic, but we stress that these identifications are made at low confidence (C = 1) and could simply be noise.…”
Section: Foreground and Background Objectsmentioning
confidence: 89%
“…We also identify a strong C iii] emitter in the southwest of the cluster (ID 4139; z = 1.9655) with a bright UV continuum and several other emission and absorption features, including Fe ii * [λ ∼ 2400,λ ∼ 2600] emission, which is useful for probing galactic winds (see e.g. Finley et al 2017). Additionally, we identify a fourth potential C iii] emitter (ID 11481; z = 2.5607) in the northeast, and three objects with weak UV absorption features (ID 6655; z = 2.1240, ID 13600; z = 2.5442, and ID 14822; z = 2.8897) at the western edges of the mosaic, but we stress that these identifications are made at low confidence (C = 1) and could simply be noise.…”
Section: Foreground and Background Objectsmentioning
confidence: 89%
“…The same is also shown in b), but galaxies with redshift z < 0.3 are excluded from the entire SDSS DR14 sample. Mg II and Fe II * emitters from the Ultra Deep Field, UDF-10, by Finley et al (2017) are shown by large symbols. In particular, Mg II emitting galaxies are denoted by large blue filled circles (where SFR values are obtained from SED fitting) and by open circles (where SFR values are obtained from the luminosity of [O II] lines).…”
Section: Dependence Of [Mg/ne] On O 32mentioning
confidence: 99%
“…The faint end of the Lyα luminosity function and its implication for reionization are presented in Paper VI (Drake et al 2017b). The properties of Fe ii* emission, as tracer of galactic winds in star-forming galaxies is presented in Paper VII (Finley et al 2017b). Extended Lyα haloes around individual Lyα emitters are discussed in Paper VIII (Leclercq et al 2017).…”
Section: Introductionmentioning
confidence: 99%